2006-2007 explosive activity and erupted products of Ubinas volcano (Peru) - Rivera Porras, Marco Antonio (2008)
1 página (Abstract) | Trabajo presentado en General Assembly, International Association of Volcanology and Chemistry of the Earth’s Interior, IAVCEI, Reykjavik, Island, 2008.